2012
DOI: 10.1086/667610
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Cell Organization in the External Region of the Olive Fruit

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Definitions of the cells that constitute the exocarp or exterior tissue of fleshy fruits are often vague, sometimes providing contradictory descriptions of the epidermis plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
(73 reference statements)
6
7
0
Order By: Relevance
“…These modifications during ripening are clearly affected by CHS silencing, since the epidermal cells from the pink sectors shared several traits common in the cells of mature green fruits: more rounded cells due to a lower tangential width and higher radial width and with thinner pegs and less cuticle invagination. A reduction in radial cell width and an increase in tangential width associated with growth also have been reported for other species, suggesting a physical stretching of the epidermis (Hammami and Rapoport, 2012). Considine and Brown (1981) showed that cell geometry is modified with the increase of internal fruit forces as a consequence of the orientation of mechanical stresses along the fruit surface.…”
Section: Chs-related Changes In Epidermal Cell Shapesupporting
confidence: 59%
“…These modifications during ripening are clearly affected by CHS silencing, since the epidermal cells from the pink sectors shared several traits common in the cells of mature green fruits: more rounded cells due to a lower tangential width and higher radial width and with thinner pegs and less cuticle invagination. A reduction in radial cell width and an increase in tangential width associated with growth also have been reported for other species, suggesting a physical stretching of the epidermis (Hammami and Rapoport, 2012). Considine and Brown (1981) showed that cell geometry is modified with the increase of internal fruit forces as a consequence of the orientation of mechanical stresses along the fruit surface.…”
Section: Chs-related Changes In Epidermal Cell Shapesupporting
confidence: 59%
“…The radial anisotropic diffusion pattern observed in the olive pericarp was similar to the grape berries close to or past véraison, indicating that the cells of the mesocarp are likewise radially elongated. This result agrees with what is known of the olive mesocarp structure [ 42 ]. The mean T 2 value of the olive was comparable to those of the grape berry pericarp tissues, as was expected for fruits with similar cellular dimensions.…”
Section: Discussionsupporting
confidence: 93%
“…The cellular structure and organisation observed in the fruit cross sections in this work respond to previous histological descriptions made by several authors in olive (Hammami & Rapoport, ; Lavee, ; Rapoport et al, ). The epidermis of the olive fruit shows a structure similar to that of other drupes, with cells of small dimensions covered with a cuticle.…”
Section: Resultssupporting
confidence: 89%
“…In the central fruit zone, the variation in the shape of the cells, from the epicarp to the endocarp, was similar to that observed in the equatorial transverse sections in this and other work of “Picual” variety (Hammami & Rapoport, ).…”
Section: Resultssupporting
confidence: 87%